Ribeira da Lage, a Stream to Protect - Tomaz, M.; Vidal, S.; Lopes, A.; Espinha, A.; Barata, C.; Parente, G.; Coito, J.; Gouveia, L. (Open Schools Journal for Open Science, 2020)
The students started by identifying the most vulnerable ecosystems in the vicinity of the school. The stream Ribeira da Lage was identified and this ecosystem was characterized and the possible sources of pollution were surveyed. Macroinvertebrates were analyzed for subsequent determination of the BMWP (Biological Monitoring Working Party) index to assess water quality. After the research work, several contacts began with local entities and institutions (CMO, ITQB; Parish Council) to raise awareness and create measures to protect the assessed and monitored ecosystem.